Examining the Bureaucracy of Halal Product Certification in Indonesia - Kasumawati, Devi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2024)
Due to the numerous instances of violations committed by Companion for Halal Products (PPH), this research was initiated. Therefore, this research aims to find out the role of PPH in the Kalimantan zone in the halal certification self-declare scheme. This study is categorized as empirical research employing a qualitative methodology. The methodology used for data collection consists of observation, interviews, and documentation. Primary data sources, including interviews with LP3H administrators, PPH, and business actors, were utilized. Meanwhile, secondary data sources include references and literature related to the research theme. From the research, it is known that in carrying out their role, PPH has a mechanism for assisting in the halal product process. In terms of field verification, it can be said that the role of PPH in the Kalimantan zone is not 100% in accordance with procedures. Multiple factors contribute to this, such as non-comprehensive understanding, low legal awareness, small survey costs, and the pressure to fulfill and accelerate Sehati quota targets imposed by Halal Product Guarantee Administering Agency (BPJPH).